2021
DOI: 10.17263/jlls.904138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complaining strategies on services offered to Facebook users on Zain Jordan

Abstract: This study aims to investigate the complaining strategies used by Facebook users on Zain Facebook page (Zain Jordan). It also aims to identify the most and least frequent strategies used by Facebook users and to examine the similarities and differences between complaining strategies found on Zain Jordan and those found in other studies in terms of types of strategies used and the linguistic features of the language. To this end, the researchers built a specialized corpus. The corpus was manually annotated to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It was revealed that complainants tended to show solidarity with student representatives as a way to encourage them to transfer the problems to university officials. In another study, Hassouneh and Zibin (2021) examined Facebook users" complaint strategies regarding Zain Jordan according to their frequency and type and the linguistic features of the language. Data were collected randomly and analyzed using pragmatic annotation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It was revealed that complainants tended to show solidarity with student representatives as a way to encourage them to transfer the problems to university officials. In another study, Hassouneh and Zibin (2021) examined Facebook users" complaint strategies regarding Zain Jordan according to their frequency and type and the linguistic features of the language. Data were collected randomly and analyzed using pragmatic annotation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The linguistic and social norms of a society govern the way its speakers use particular linguistic expressions to carry out certain speech functions (Banikalef, 2021). Strategies are used to express the meanings of intended messages among speakers (Hassouneh & Zibin, 2021). Accordingly, in suicide notes, Chaski (2012) proposes six elements of texts that can found in them, which are apology, love, anger, complaint, business, and trauma.…”
Section: Literature Reviewmentioning
confidence: 99%